Meteorological Observations at Syowa Station in 1978 by the 19th Japanese Antarctic Research Expedition - Masahiro Yasuda; Ryuji Sato; Takashi Matsumoto; Susumu Kaneto (National Institute of Polar Research, 1980)
This paper describes the results of surface and aerological meteorological observations at Syowa Station (69°00'S, 39°35'E) between 1 February 1978 and 31 January 1979. The main subjects of the observations, methods, and equipments are the same as in 1977 except the use of hydrogen generator at the station. According to the WMO procedures, the surface and aerological data were immediately reported to the World Meteorological Center in Melbourne via Mawson Station. This paper also gives the results of experiment on the influence of sunshine upon the sonde thermistors, statistical discussion on the stratospheric sudden warming using the data of the last 13 years and analytical research of mesoscale cyclonic activities observed at Syowa Station.